DECOMPOSITION OF COMPLETE GRAPHS AND COMPLETE BIPARTITE GRAPHS INTO COPIES OF Pn3 or S2Pn3 AND HARMONIOUS LABELING OF K2+ Pn - P. Selvaraju; G. Sethuraman (IndoMS, 2011)
Pdf AbstractDOI : http://dx.doi.org/10.22342/jims.0.0.23.109-122